2012
DOI: 10.1016/j.neuroimage.2012.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Decoding covert spatial attention using electrocorticographic (ECoG) signals in humans

Abstract: This study shows that electrocorticographic (ECoG) signals recorded from the surface of the brain provide detailed information about shifting of visual attention and its directional orientation in humans. ECoG allows for the identification of the cortical areas and time periods that hold the most information about covert attentional shifts. Our results suggest a transient distributed fronto-parietal mechanism for orienting of attention that is represented by different physiological processes. This neural mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 56 publications
8
47
0
Order By: Relevance
“…Therefore, our approach for electrode projection, which is identical to that presented by Hermes and colleagues (Hermes et al, 2010) for the special case of electrode strips, could be not as accurate as in previous works based on more advanced and precise methods (see, e. g., Dalal et al, 2008;Dykstra et al, 2012;Hermes et al, 2010;Swann et al, 2009;Tertel et al, 2011). Finally, while the cortical surface of the brain is the usual and ideal target space of fMRI analyses (see, e. g., Gunduz et al, 2012;Miller et al, 2007b), and projecting the iEEG electrodes on the cortical surface permits the CBA application to correct the channel positions on the group average cortical space, it should be also remarked that whenever the electrodes are not placed accurately along a sulcus, as could be the cases for electrode grids or arrays, the possible bias for the projection on the cortical surface is potentially higher than for the projection on the envelope surface of the brain, which can be seen as a less biased solution for electrode grids or arrays.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, our approach for electrode projection, which is identical to that presented by Hermes and colleagues (Hermes et al, 2010) for the special case of electrode strips, could be not as accurate as in previous works based on more advanced and precise methods (see, e. g., Dalal et al, 2008;Dykstra et al, 2012;Hermes et al, 2010;Swann et al, 2009;Tertel et al, 2011). Finally, while the cortical surface of the brain is the usual and ideal target space of fMRI analyses (see, e. g., Gunduz et al, 2012;Miller et al, 2007b), and projecting the iEEG electrodes on the cortical surface permits the CBA application to correct the channel positions on the group average cortical space, it should be also remarked that whenever the electrodes are not placed accurately along a sulcus, as could be the cases for electrode grids or arrays, the possible bias for the projection on the cortical surface is potentially higher than for the projection on the envelope surface of the brain, which can be seen as a less biased solution for electrode grids or arrays.…”
Section: Discussionmentioning
confidence: 91%
“…including those responsible for impressing and retriev ing memory engrams [22,34,38,[42][43][44]. In view of this, characteristics of the classical EEG frequency range seem to be the most promising in the general NFB case.…”
Section: Changes In Eeg Spectral Characteristics In the Course Of Neumentioning
confidence: 99%
“…Gunduz et al [71, 72] showed that ECoG could identify cortical areas and time periods that hold the most information about covert attentional shifts. ECoG was recorded when subjects covertly attended to a spatial location and responded to contrast changes in the presence of distractors in a cueing task.…”
Section: Ecog Cognitive Neurosciencementioning
confidence: 99%